Limitative Changes in Indictment Letter After Constitutional Court Decision Number 28/PUU-XX/2022 as a From of Legal Certainty Guarantee - Rahayu, Mutia Dwi; Marpaung, Devi Siti Hamzah (Universitas Islam Lamongan, 2023)
In the preparation of the indictment, accuracy and are needed. This is because the indictment is used as the basis for the judge in determining the limits of the examination at trial. Indictments that are not qualified for formal and material will have the status of being voidable and charges that are null and void. This study aims to describe and clearly know what makes the reasons for the cancellation of the indictment letter and the legal certainty of the indictment letter after the Constitutional Court ruling. Normative juridical methods and library research techniques with the introduction of laws and regulations and conceptuals are the choices of researchers in this study. The results showed that non-fulfillment of the formal conditions, namely the conditions relating to the identity of the defendant, resulted in the charges being dropped being dropped. Meanwhile, the material requirements are related to a careful, clear, and complete description of the criminal act charged, which in fulfillment of the material conditions is not met, the charges filed can be null and void. Article 144 of the Criminal Code provides for the provision of changing the letter of indictment once without any limitative arrangement for changing the substance of the indictment. After the 2022 Constitutional Court Decision, the Public Prosecutor has limitations in changing the substance of the indictment as a form of certainty and legal justice as Amar Decision Number 28 / PUU-XX / 2022.